(untitled) (Journal of Dhaka Medical College, 2017)
Obstructive sleep apnea (OSA) is one of the most common causes of sleep disordered breathing in children. However, it is associated with significant morbidity, potentially impacting on long term neurocognitive and behavioural development, as well as cardiovascular outcomes and metabolic homeostasis. Diagnosis and treatment of this condition in children differs in many aspects from that in adults. In this review article, we will describe the pathophysiology, clinical features and laboratory testing and measures needed for treatment of this disease. J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 124-128